TAMAN OLAHRAGA REKREASI DI BANJARBARU - Rijal, Fahrul; Sa'ud, Mohammad Ibnu (JURNAL TUGAS AKHIR MAHASISWA LANTING, 2022)
Physical exercise is one of the most important activities to do considering the many benefits that result from exercising, both in terms of the physical and spiritual health aspects of a person. However, due to various factors such as laziness, lack of adequate physical exercise facilities, and the location of each physical exercise facility which is separate from each other, the interest of the Banjarbaru community in physical exercise is low. Banjarbaru Recreational Physical Exercise Park is the answer to this problem. This area is the form of a thematic park that aims to accommodate various types of physical exercise and at the same time as an interactive recreation facility in an integrated area so that people will be able to exercise in a recreational way. In accordance with its objectives, the Banjarbaru Recreational Physical Exercise Park consists of two main functions, namely as a forum that facilitates recreational physical exercise activities and as a recreational facility to attract the interest of the Banjarbaru community to come and exercise. The Superimposition method was chosen as the solution method because it combines and collides two spatial programs in this context in the form of recreational and recreational physical exercise in which each spatial program will be contaminated with each other and form a new pattern so that it will realize the goals to be achieved.